Phylogenetic tree of Kuantan cattle by DNA barcoding - . Hidayati; R. Misrianti; A. Ali (Jurnal Ilmu Ternak dan Veteriner, 2016)
Kuantan cattle is one of local beef cattle breed of Riau Province which its origin was unknown. Kuantan cattle are commonly found in Indragiri Hulu and Kuantan Singingi Regency. Based on phenotype characterizations, kuantan cattles are similar with pesisir cattle (West Sumatera beef cattle). Historically, kuantan cattle were pesisir cattle brought by “minang” immigrants (Immigrant from West Sumatera) to this region. The purpose of this study was to analyze the origin of the kuantan cattle through genetic diversity analysis using DNA barcode. DNA barcode used was Cytochrome oxidase subunit I gene which was found in the mtDNA. DNA isolation was done on 25 kuantan’s blood samples and 18 pesisir blood samples. Amplification of COI gene segment used Polymerase Chain Reaction technique. The forward primer sequence used in this study was F’5 TTCTCAACCAACCATAAAGATATTGG-3’ and the reverse primer sequence used was reverse 5’-TAGACTTCGGGGTGTCCAAAGAATCA-3. It squeezed kuantan and pesisir sequence 5711 - 6420 base (GeneBank accession number NC_005971) with length by 710 bp. Analysis result of sequence using MEGA 5.2 Program showed that there were 6 polymorphic sites establishing 7 haplotypes on kuantan cattle and 9 polymorphic sites establishing 12 haplotypes on pesisir cattle. Based on genetic distance and phylogeney tree, kuantan and pesisir cattle were in same group with Bos indicus. Mutation in the COI gene segment in this study was too small and was not able to distinguish the difference of those breeds. The result of neighbor joining analyze indicated that kuantan cattle origin was from Bos indicus just like pesisir cattle.Key Words: COI Gene, Polymorphic, Kuantan Cattle, Genetic Distance, Phylogenetic Tree